BALANCING BETWEEN HEAD AND HEART: A STRATEGY OF CHARACTER EDUCATION IN ELT - Irwandi Irwandi (Fakultas Bahasa dan Seni Universitas Negeri Padang, 2014)
Character education which is variously known as values education, moral education, and transmission of core values is regarded as one of the important aspects in education. In Indonesia, character education has become a central theme of Indonesian education since 2010 which is included into School Based Curriculum (KTSP). Moreover, character education is mentioned in the objectives of national education and considered as the basis of the vision of national building to create a society which is characterized by good deeds, moral, ethics, culture, and good civilization. One of strategies in the character education is through the reactivation of the current curriculum which has already contained character education. English as one of compulsory subjects in the curriculum of Indonesian education can be a vehicle to explore values which are taught in character education. Thus, English language teaching (ELT) does not merely focus on how to lead the learners are competent in the language skills, but also guide them to internalize the values for character building. This paper highlights some strategies of character education in English language teaching. The discussion specifically is directed to the strategy of integration of character education into English teaching in terms of course design, instructional materials, classroom technique, and classroom management. Keyword: character education, core values, contextual teaching and learning (CTL)